PERAN DINAS SOSIAL DALAM PENANGANAN ORANG DALAM GANGGUAN JIWA (ODGJ) DI KOTA MEDAN - Aridho, Ahmad; Nainggolan, Mangido (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to analyze the role of the Social Affairs Office (Dinas Sosial) in the management of People with Mental Disorders (ODGJ) in Medan City. Mental health issues have become a critical concern in social policy, particularly given the increasing number of untreated ODGJ in urban areas. Employing a qualitative research method with a policy politics approach, this study examines how local government policies are operationalized through the Social Affairs Office and evaluates the extent to which this institution addresses the need for rehabilitation and social protection for individuals with mental disorders. Data were collected through in-depth interviews with key informants, including Social Affairs Office personnel, families of ODGJ, and community figures. The data analysis process followed three fundamental stages: data reduction, data display, and data verification, aiming to construct a comprehensive and in-depth understanding of the phenomenon. The findings reveal that the role of the Social Affairs Office in Medan remains limited, predominantly reactive, and lacks systemic integration across institutions. Major obstacles include inadequate rehabilitation infrastructure, and weak communication with the community. This study underscores the urgent need for institutional reform and strengthened intersectoral collaboration to ensure that services for ODGJ are more humane, structured, and sustainable. ABSTRAKPenelitian ini bertujuan untuk menganalisis peran Dinas Sosial dalam penanganan Orang Dalam Gangguan Jiwa (ODGJ) di Kota Medan. Isu kesehatan jiwa menjadi perhatian serius dalam kebijakan sosial karena meningkatnya jumlah ODGJ yang tidak tertangani secara layak, terutama di wilayah perkotaan. Penelitian ini menggunakan metode kualitatif dengan pendekatan politik kebijakan untuk menelaah bagaimana kebijakan pemerintah daerah diimplementasikan melalui Dinas Sosial, serta sejauh mana lembaga ini mampu menjawab kebutuhan rehabilitasi dan perlindungan sosial bagi ODGJ. Pengumpulan data dilakukan melalui wawancara mendalam dengan informan dari pihak Dinas Sosial, keluarga ODGJ, serta tokoh masyarakat. Teknik analisis data dilakukan melalui tiga tahap utama, yaitu reduksi data, penyajian (display) data, dan verifikasi data untuk memperoleh pemahaman yang mendalam dan menyeluruh. Hasil penelitian menunjukkan bahwa peran Dinas Sosial Kota Medan dalam penanganan ODGJ masih bersifat terbatas, reaktif, dan belum terintegrasi secara optimal antar lembaga. Keterbatasan fasilitas rehabilitasi, serta lemahnya komunikasi dengan masyarakat menjadi hambatan utama. Penelitian ini menegaskan perlunya pembenahan kelembagaan dan penguatan kerja sama lintas sektor agar pelayanan terhadap ODGJ lebih manusiawi, sistematis, dan berkelanjutan.